Increasing the performance of the raw material wheel and fiber quality when processed by the sawing machine - Safarov Askarbek; Narmatov Elmurod; Burieva Sojida; Usmonov Islomiddin (E3S Web of Conferences, 2023)
The saw gin, the primary technical device used in the cotton ginning process, is responsible for separating the cotton fiber from the cotton seed. After being cleansed of khaschops and dried to the desired humidity in the drying, cleaning, and cleaning shops, seeded cotton is transferred to the main building of the business for ginning (separation of fiber). Up to now, 4DP-130, 5DP-130, and DPZ saw gins have been employed in cotton ginning operations to spin medium fiber seeded cotton. The ginning machine's operation, which separates the fiber from the seed in cotton gins, is largely responsible for the creation of high-quality fiber. Maintaining natural quality indicators during the technical process of first processing of cotton, i.e. the appearance, length, and presence of minute impurities in the fiber, is key to ensuring the competitiveness of cotton fiber produced in our nation on the global market. One of the most crucial processes is the ginning of seeded cotton with the appropriate amount of moisture and dirt, which involves removing the fiber from the seed. The length of the fiber, the impurities in the content, the absence of damage, and the hairiness of the seed all play a significant role in this process.